1996
DOI: 10.1074/jbc.271.44.27193
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Preliminary Diffraction Data of a Major Pollen Allergen

Abstract: Group V major allergen Phl p 5b of timothy grass pollen induces allergic rhinitis and bronchial asthma in 90% of grass pollen-allergic patients. In addition to its allergenicity ribonuclease activity has recently been attributed to this 29-kDa protein.The allergen was expressed in Escherichia coli and subsequently purified. Spontaneous conversion of these preparations to a mixture of various forms with molecular sizes between 10 and 29 kDa was consistently observed. Surprisingly, crystals could be grown from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…The 25-kDa fraction had an apparent M r of 12 kDa and was thought (but not confirmed) to be a degradation product [5]. Another indication for the existence of a group 5 degradation product was reported by Bufe et al [23]. They observed the spontaneous appearance of a C-terminal peptide of around 12 kDa after Phl p 5b expression in Escherichia coli.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…The 25-kDa fraction had an apparent M r of 12 kDa and was thought (but not confirmed) to be a degradation product [5]. Another indication for the existence of a group 5 degradation product was reported by Bufe et al [23]. They observed the spontaneous appearance of a C-terminal peptide of around 12 kDa after Phl p 5b expression in Escherichia coli.…”
Section: Introductionmentioning
confidence: 79%
“…Whether the C-terminus of Dac g 5 is generated posttranslationally, by proteolytic activity, or whether the peptide has its own gene is not known. So far, there are no reports showing that the natural allergen is degraded to its C-terminal half, except for two recombinant Phl p 5 products [23, 45]. Maglio et al [45]reported a time-dependent degradation of the N-terminus of rPhl p 5a.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations